If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + -3 = -12 Reorder the terms: -3 + 3u = -12 Solving -3 + 3u = -12 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3u = -12 + 3 Combine like terms: -3 + 3 = 0 0 + 3u = -12 + 3 3u = -12 + 3 Combine like terms: -12 + 3 = -9 3u = -9 Divide each side by '3'. u = -3 Simplifying u = -3
| (x^2)-9= | | -3x-2=7x+4 | | 100=2.5x | | 5z=60 | | 1.6q-3.5-5.2q=-4.6q-5.4 | | 4x+10=x+3(3x+3)+1 | | 12x^2+41x+24=0 | | 5x+29y=-19 | | 2(n+2)=3n+9 | | x*6+47=x*11-8 | | x^3-70x^2+1500x-10800=0 | | 5(y-1)=7(3+y) | | 18x^2-9x-20=0 | | b^2+3=5b-3 | | 58-6x=3x+19 | | x^2+36=100 | | 8-2a=2 | | -3-2(y+4)=3y-(4y-5) | | 12x^2+43x+36=0 | | 5(2x+n)=2(n-1) | | 47=-62 | | 10x+6x= | | 29+18=-59-3 | | 3x=5y+2 | | 3(2x-1)=11-x | | 4y-4=6-7y | | 18x-3=51 | | 18y=15(y-8) | | -4x-12=13+x | | 5m+8-2m=17+4m-3 | | 5y=x+17 | | 6m-12m=1-4 |